2012
DOI: 10.1590/s1413-35552012005000048
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic patients with and without peripheral neuropathy reveal different hip and ankle biomechanical strategies during stair descent

Abstract: Background: The progression of diabetes and the challenge of daily tasks may result in changes in biomechanical strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…Muscle weakness and alterations to muscle structure may lead to altered walking ability even in people without diabetic neuropathy . Slower walking speed, shorter step length and wider step width have all been demonstrated in people without diabetic neuropathy , and we have recently shown reduced lower limb strength and altered muscle structure in people with Type 2 diabetes and minimal neuropathy .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Muscle weakness and alterations to muscle structure may lead to altered walking ability even in people without diabetic neuropathy . Slower walking speed, shorter step length and wider step width have all been demonstrated in people without diabetic neuropathy , and we have recently shown reduced lower limb strength and altered muscle structure in people with Type 2 diabetes and minimal neuropathy .…”
Section: Introductionmentioning
confidence: 80%
“…Walking impairment is perceived to be a late complication of diabetes, as it has been described primarily in people with established neuropathy ; however, a number of studies have shown walking impairment in people with diabetes before the onset of large‐fibre neuropathy . This suggests that either neuropathy may not be the only contributor to this abnormality or that small‐ rather than large‐fibre neuropathy may be a contributing factor.…”
Section: Introductionmentioning
confidence: 99%
“…(13) . O exercício apresenta benefícios, tais como os níveis mais elevados de flexibilidade, função cardiorrespiratória e neuromuscular que permitem ao ser humano ser mais ativo e aumentar o nível de atividades realizadas, obtendo maior autonomia (2) .…”
Section: Resultsunclassified
“…Os pressupostos de normalidade foram confirmados pelo teste de Kolmogorov-Smirnov a análise de variância fatorial (ANOVA para medidas repetidas) foi utilizada para a comparação intra e intergrupos, sendo considerados significantes valores de P < 0,05. Calculou-se o effect size por meio do teste "d de Cohen" a fim de quantificar a magnitude dos efeitos entre os grupos, no qual o valor foi classificado como pequeno se 0,20≤d≤0,5; médio 0,5≤d≤0,8; grande d≥0,8 (13)(14) . Foram utilizados os programas Microsoft Excel® 2003 e GraphPadPrism®.…”
Section: Figura 1 Fluxograma Do Estudounclassified
“…39 The inclusion of occupational therapists, physical therapists, and registered nutritionists further facilitates the respective home environment augmentation, mobility, dietary, and health style modifications necessary to reach the personalized goals of the high-risk diabetic patient. [40][41][42] …”
Section: The Role Of the Multidisciplinary Teammentioning
confidence: 99%